2018
DOI: 10.1111/cas.13792
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive role for kinases phosphorylating p53 in DNA damage‐induced apoptosis

Abstract: Tumor suppressor p53 plays an important role in cancer prevention. Under normal conditions, p53 is maintained at a low level. However, in response to various cellular stresses, p53 is stabilized and activated, which, in turn, initiates DNA repair, cell‐cycle arrest, senescence and apoptosis. Post‐translational modifications of p53 including phosphorylation, ubiquitination, and acetylation at multiple sites are important to regulate its activation and subsequent transcriptional gene expression. Particularly, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 74 publications
(164 reference statements)
3
82
0
Order By: Relevance
“…Although DYRK2 distinct role in cancer development has been broadly proved, there is controversy concerning its pro-or anti-tumour potentials. However, various studies have shown that DYRK2 is down-regulated in various cancer tissues such as lung, breast, prostate and colon, associated with poor patient prognosis [32,50,[65][66][67][68][69]. The data showing the correlation in the levels of both proteins in tumour tissue (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Although DYRK2 distinct role in cancer development has been broadly proved, there is controversy concerning its pro-or anti-tumour potentials. However, various studies have shown that DYRK2 is down-regulated in various cancer tissues such as lung, breast, prostate and colon, associated with poor patient prognosis [32,50,[65][66][67][68][69]. The data showing the correlation in the levels of both proteins in tumour tissue (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Particularly, phosphorylation of p53 protein plays a critical role in modulating its activation to induce apoptosis in cancer cells. 8 TP53 activity decreases or disappears in cancer cells. The TP53 gene contains mutations in~50-60% of human cancers.…”
Section: Introductionmentioning
confidence: 98%
“…While it is almost undetectable in cells with normal protein levels, its expression increases in the presence of stress. The cells without stress are inactive . Thanks to the response it creates after cellular stress, TP53 affects functions of genes stopping cell cycle, leading to apoptosis, responsible for DNA repair and associated with aging and cellular metabolism .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations